PTU-035 Development and Initial Validation of Prognostic Scoring Systems for lower Gastrointestinal Bleeding. (4th June 2013) - Smith, C; Thompson, J M; Vijayan, B; Fraser, A; El-Omar, E M; Leeds, J S
Abstract : Introduction: Lower gastrointestinal bleeding (LGIB) is a common and heterogeneous condition, in which there is a paucity of data concerning predictors of adverse outcomes. This study aimed to identify independent risk factors for adverse outcomes in LGIB, and derive prognostic scoring systems to stratify patients by risk on admission. Methods: The Aberdeen bleeding unit opened in 1991 and has recorded demographics, presenting features, haemodynamic status and outcomes on all admissions in a comprehensive database. Analysis was performed on admissions due to LGIB over the period 1991 to 2005. Independent risk factors for re-bleeding, requirement for surgical intervention, and mortality at 30 days were elucidated by means of univariate and multivariate binary logistic regression analyses. Risk factors were then modelled into simple numerical prognostic scoring systems which underwent preliminary validation tests in order to determine their predictive performance using receiver operating curve analysis. Results: Over the study period, 2385 patients were admitted with LGIB. Re-bleeding was experienced in 322 (13.5%), 135 (5.7%) required surgery and 129 (5.6%) died within 30 days of admission. Multivariate analysis revealed that re-bleeding was associated with inpatient status at the time of initial bleed (OR 1.8; 95% CIs 1.3–2.5), age 60–79 (OR 1.5; 95% CIs 1.0–2.3), age > 80 (OR 2.1; 95% CIs 1.3–3.2), syncope (OR 2.3; 95% CIs 1.5–3.6), underlying malignancy (OR 2.1; 95% CIs 1.0–4.3), hypotension (OR 2.3; 95% CIs 1.4–3.6) and haemoglobin < 10g/dL (OR 5.0; 95% CIs 2.8–8.9). 30 day mortality was associated with inpatient status at the time of initial bleed (OR 3.3; 95% CIs 2.0–5.4), age 60–79 (OR 3.3; 95% CIs 1.5–7.1), age > 80 (OR 6.0; 95% CIs 2.6–13.7), underlying liver disease (OR 7.2; 95% CIs 2.9–17.7), hypotension (OR 2.9; 95% CIs 1.5–5.3), and tachycardia (OR 2.1; 95% CIs 1.3–3.6). No independent risk factors were identified for the requirement of surgery. Separate prognostic scoring systems (0–7) were created for re-bleeding and mortality outcomes, with area under ROC curves 0.742 and 0.802 respectively. A score of 0 reflected a re-bleeding risk of 1.1% and 30 day mortality of 0.0%, whereas a score of 6 reflected a re-bleeding risk and 30 day mortality risk of 50% in both scoring systems. No patients scored the highest risk grade of 7 in either model. Conclusion: These scoring systems can be used to calculate re-bleeding risk and 30 day mortality in patients with LGIB. Further external validation and confirmation is required. Disclosure of Interest: None Declared